2017
DOI: 10.1128/jcm.00254-17
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility Testing of Aspergillus spp. by Using a Composite Correlation Index (CCI)-Based Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry Method Appears To Not Offer Benefit over Traditional Broth Microdilution Testing

Abstract: Aspergillus spp. cause serious invasive lung infections, and Aspergillus fumigatus is the most commonly encountered clinically significant species. Voriconazole is considered to be the drug of choice for treating A. fumigatus infections; however, rising resistance rates have been reported. We evaluated a matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS)-based method for the differentiation between wild-type and non-wild-type isolates of 20 Aspergillus spp. (including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 24 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…including A. fumigatus [40]. In a proof-of-concept study, MALDI-TOF MS was shown to accurately detect strains of A. fumigatus with reduced voriconazole susceptibility, although this method did not prove to be more rapid or simpler compared to testing with PCR and the Sensititre® microdilution panel [41]. Still, this method needs improved standardization, expanded availability of databases, and databases need to be continuously updated to include reference spectra of unusual pathogens [42, 43].…”
Section: Culture-based Methods For Detection Of Resistance In Aspergimentioning
confidence: 99%
“…including A. fumigatus [40]. In a proof-of-concept study, MALDI-TOF MS was shown to accurately detect strains of A. fumigatus with reduced voriconazole susceptibility, although this method did not prove to be more rapid or simpler compared to testing with PCR and the Sensititre® microdilution panel [41]. Still, this method needs improved standardization, expanded availability of databases, and databases need to be continuously updated to include reference spectra of unusual pathogens [42, 43].…”
Section: Culture-based Methods For Detection Of Resistance In Aspergimentioning
confidence: 99%
“…In line with our studies [ 67 , 68 , 69 ], slightly longer incubation times (30 and 48 h) allowed for accurate detection of isolates as WT or non-WT by MS-AFST, in complete agreement with the CYP51A gene sequence analysis results. Remarkably, using the “three-point” assay (no drug, 16 μg/mL voriconazole, and voriconazole ECV), the authors [ 73 ] obtained the same findings, requiring 30 to 48 h of incubation with the drug prior to MALDI-TOF MS analysis. It is likely that some fungal isolates requiring additional time relates to the impossibility of their reaching enough growth and, consequently, level of expressed proteins to allow for correct classification by the MS-AFST assay [ 69 , 73 ].…”
Section: Nonconventional Phenotypic Assays For Testing Fungal Suscmentioning
confidence: 80%
“…Remarkably, using the “three-point” assay (no drug, 16 μg/mL voriconazole, and voriconazole ECV), the authors [ 73 ] obtained the same findings, requiring 30 to 48 h of incubation with the drug prior to MALDI-TOF MS analysis. It is likely that some fungal isolates requiring additional time relates to the impossibility of their reaching enough growth and, consequently, level of expressed proteins to allow for correct classification by the MS-AFST assay [ 69 , 73 ].…”
Section: Nonconventional Phenotypic Assays For Testing Fungal Suscmentioning
confidence: 80%
See 1 more Smart Citation
“…Spectra from different concentrations of the antifungal substance are used to create a composite correlation index (CCI) and thereby infer a Minimal Profile Change Concentration (MPCC) analogous to an MIC value. Some studies also evaluated a simplified three-point assay, in which fungal spectra at the breakpoint concentration were compared to a maximum concentration as well as a drug-free control, and were then classified into resistant or susceptible depending upon their similarity to one of the extremes [ 16 , 21 , 23 , 25 , 30 ]. However, while the hands-on time is somewhat shortened, the time to result mainly depends on the incubation time, and is thereby not abbreviated.…”
Section: Discussionmentioning
confidence: 99%